In vitro Toxicity Testing in the Twenty-First Century - Roggen, Erwin L. (Frontiers in Pharmacology, 2011)
The National Research Council (NRC) article “Toxicity Testing in the 21st Century: A vision and A Strategy” (National Research Council, 2007) was written to bring attention to the application of scientific advances for use in toxicity tests so that chemicals can be tested in a more time and cost efficient manner while providing a more relevant and mechanistic insight into the toxic potential of a compound. Development of tools for in vitro toxicity testing constitutes an important activity of this vision and contributes to the provision of test systems as well as data that are essential for the development of computer modelling tools for e.g. system biology, physiologically-based modelling. This article intends to highlight some of the issues that have to be addressed in order to make in vitro toxicity testing a reality in the 21st century.